Associations of overweight and metabolic health with successful aging: 32-year follow-up of the Helsinki Businessmen Study. Issue 5 (May 2020) - Jyväkorpi, Satu K.; Urtamo, Annele; Strandberg, Arto Y.; von Bonsdorff, Mikaela; Salomaa, Veikko; Kivimäki, Mika; Luotola, Kari; Strandberg, Timo E.
Summary: Background & aims: Prognostic significance of metabolically healthy overweight and obesity (MHO) is under debate. However the relationship between MHO and health-related quality of life (HRQoL) is less studied. We compared successful aging (longevity plus HRQoL) in men with MHO, metabolically healthy normal weight (MHN) and metabolically unhealthy overweight and obesity (MUO). Methods: In the Helsinki Businessmen Study longitudinal cohort, consisting of men born 1919 to 1934. In 1985/86, overweight (BMI≥25 kg/m 2 ) and metabolic health were determined in 1309 men (median age 60 years). HRQoL was assessed using RAND-36/SF-36 in 2000 and 2007, and all-cause mortality retrieved from registers up to 2018. The proportion of men reaching 90 years was also calculated. Results: Of the men, 469 (35.8%), 538 (41.1%), 276 (21.1%), and 26 (2.0%) were MHN, MHO, MUO and MUN, respectively. During the 32-year follow-up, 72.3% men died. With MHN as reference, adjusted hazard ratio with all-cause mortality was 1.08 (95% confidence interval [CI] 0.93 to 1.27) for MHO, and 1.18 (95% CI 0.95 to 1.47) for MUO. During follow-up, 273 men reached 90 years. With MHN as reference, adjusted odds ratio for MHO was 0.82 (95% CI 0.59 to 1.14) and 0.62 (95% CI 0.41 to 0.95) for MUO. Men in MHN group scored generally highest in RAND-36 HRQoL subscales in 2000 and 2007, of those significantly better in Physical functioning, Role physical, Role emotional, Bodily Pain, and General health sub-scales compared to MHO group in 2000. Conclusions: As compared to MHN, MHO in late midlife does not increase mortality, but impairs odds for successful aging. Highlights: Metabolically unhealthy obesity (MHO) in late midlife did not increase mortality in this study. MHO impaired odds for successful aging defined as longevity and Health Related Quality of Life. Those with metabolically healthy normal weight (MHN) at baseline had better quality of life at old age than those with MHO. Men with MHN had higher odds of reaching 90 years than those men with MHO or MUO at baseline.